Engineering a commercial soybean inoculant to efficiently degrade glyphosate - Brambilla, Silvina Maricel; Pascuan, Cecilia Gabriela; Frare, Romina Alejandra; Liebrenz, Karen Ivana; Pesquero, Natalia; Ruiz, María Juana; Soto, Gabriela Cynthia; Cristos, Diego Sebastian; Ayub, Nicolás Daniel (Elsevier, 2025)
Nitrogen-fixing rhizobia possess the well-characterized phn operon, which encodes the C–P lyase enzymatic complex responsible for degrading phosphonates such as glyphosate. However, glyphosate exerts a bacteriostatic effect on these endosymbionts, hindering the activation of this natural degradation pathway and thereby limiting its multiple potential benefits within glyphosate-tolerant cropping systems. In this study, we characterized a mutant derived from the commercial inoculant Bradyrhizobium japonicum E109, carrying a single-nucleotide substitution causing a Ser100Ala change in lactate dehydrogenase. This mutation enhances the detoxification of methylglyoxal, a toxic byproduct induced by glyphosate, and, importantly, enables the mutant strain to efficiently degrade glyphosate and improve crop productivity. Since inoculation is routine in soybean (Glycine max (L.) Merr.) production, this strategy adds no additional cost, benefiting farmer profitability as well as the environment and public health.